On how E. Cummings uses overprotection and victimization strategies to subvert patriarcal tradition - González Mínguez, María Teresa (CUADERNOS KÓRE, 2011)
Modernist writers adopted strategies such as associating women with dreadful prototypes; slandering them in essays, memoirs and poems and ignoring their achievements in critical texts. Among the general flux of modernist authors, the American E. E. Cummings wrote a large variety of poems in which he venerates his lady. However, this veneration can be as chauvinist as the most aggressive words against women. By using humour and satire, Cummings presents himself as a protector, an adviser, a victim and the reformer of an old-fashioned patriarchal culture.The purpose of this article is to prove how, by emphasizing overprotection and victimization, Cummings subverts male and female roles, criticizes those men who treat women with disdain and, at times, recognizes his own prejudices against a particular kind of women. In order to demonstrate it, I will analyse some poems written throughout his career such as "my love is building a building" or "supposing i dreamed this)." Various articles in Spring. The Journal of the E. E. Cummings Society, Richard Kennedy's and Christopher Sawyer-Lauçanno's biographies of Cummings as well as other publications such as Maurice Berger's Constructing Masculinity or  Jósep Armengol and Ángels Carabí's Debating Masculinty will be used to support how Cummings' revolutionary techniques contribute to subvert patriarchal traditions and open new directions in male and female roles.
Keywords: Victimization; overprotection; male and female roles; patriarchal traditions; new directions